Digital Hospitality: Integrating the Local Culture of Hidup Orang Basudara for Interreligious Dialogue in Maluku - Sopacuaperu, Eklepinus Jefry; Pieter, Jenne J. R.; Nanuru, Ricardo Freedom (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2025)
This article aims to delve into the community’s cultural values, exemplified by the ethos of “hidup orang basudara” (living together as brothers and sisters) which embodies hospitality in Maluku’s multicultural and multi-ethnic communities. By recognizing hospitality as fundamental necessary for the development of continuous inter-religious dialogue, an elaborate and creative exploration of the philosophy of “hidup orang basudara” is conducted. Using a literature review approach encompassing selected books, scholarly journals, and previous research, depth interview, observation, this article analyzes and interprets data to enrich the discourse on alternative pathways for continuous inter-religious dialogue in Ambon- Maluku. The result of this study show that the philosophy of “hidup orang basudara” gas bacome an alternative developments in continuous inter-religious dialogue in Maluku can enrich the praxis of inter-religious dialogue efforts aimed at nurturing peace in the land of Maluku. The integration of local culture and digital innovation forms a “digital hospitality” that strengthens interfaith tolerance in the city of Ambon and promotes sustainable interreligious dialogue.